Primer Design to Sequence Analysis - a Pipeline for a Molecular Genetic Diagnostic Laboratory - Doherty, Elaine; Marquis-Nicholson, Renate; Love, Jennifer M.; Brookes, Clare; Prosser, Debra; Love, Donald R. (IntechOpen, 2011)
None